Wanprestasi Perjanjian Hutang Piutang Dengan Objek Jaminan Sertifikat Hak Milik Atas Nama Orang Lain: Studi Putusan Nomor 8/Pdt.G/2023/PN.Praya - Jannatun, Baiq Haulia; Wahyuningsih, Wiwiek (Fakultas Hukum Universitas Mataram, 2024)
The main objectives this research is to determine the concept of granting credit with Ownership Certificate in the name of another person, as well as the considerations of the Judge in Decision Number 8/Pdt.G/2023/PN.Praya. This study classified as normative legal research. Based on the results obtained, it is shows that the concept of granting credit with others' Ownership Certificate is as follows: firstly, the bank shall adhere to the principle of prudence; secondly, the making of a Deed of Mortgage concerns to ensure legal certainty; lastly, the registration of the latter deed is indeed aims to obtain legal certainty. In Decision Number 8/Pdt.G/2023/PN.Praya, the judge granted some of the plaintiff's claims, one of which stated that the defendant had committed a breach of contract, as stated in the judge's considerations Number 24. From the principle of legal certainty, the decision in this case seems appropriate. However, from the principles of justice and legal protection, it is less appropriate, namely the dismissal of the plaintiff's claim in the form of seizing the collateral, which should have been possible because the defendant was proven to have committed a breach of contract.